1994
DOI: 10.1115/1.2929423
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Measurements of Local Heat Transfer Coefficient and Adiabatic Wall Temperature Beneath an Array of Impinging Jets

Abstract: A transient method of measuring the local heat transfer under an array of impinging jets has been developed. The use of a temperature-sensitive coating consisting of three encapsulated thermochromic liquid crystal materials has allowed the calculation of both the local adiabatic wall temperature and the local heat transfer coefficient over the complete surface of the target plate. The influence of the temperature of the plate through which the impingement gas flows on the target plate heat transfer has been qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(13 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The transient liquid crystal method using 1-D heat conduction scheme has been widely employed for jet impingement heat transfer studies; for example, the measurements conducted by Van Treuren et al [16] and Hwang and Cheng [17]. More complete procedures are employed in the three-temperature film cooling problem such as proposed by Vogel et al [18], and Chambers et al [19].…”
Section: -D Inverse Transient Liquid Crystal Methodsmentioning
confidence: 99%
“…The transient liquid crystal method using 1-D heat conduction scheme has been widely employed for jet impingement heat transfer studies; for example, the measurements conducted by Van Treuren et al [16] and Hwang and Cheng [17]. More complete procedures are employed in the three-temperature film cooling problem such as proposed by Vogel et al [18], and Chambers et al [19].…”
Section: -D Inverse Transient Liquid Crystal Methodsmentioning
confidence: 99%
“…In Fig. 9, the present measurements of mean Nusselt number are compared with the previous data [10,11]. The present data provide information in a relatively lower Re range.…”
Section: Effects Of Jet Aspect Ratio With Flow Exit At Two Ends (Exf-2)mentioning
confidence: 51%
“…Detailed heat transfer distributions under arrays of jets impinging on a target plate with dimpled or film hole surfaces were investigated by Treuren et al [10] and Han and his colleagues [11][12][13] using a liquid crystal image technique. They found that the crossflow and the exit flow direction significantly affect the heat transfer distributions on a target surface.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts have been made to optimize each method in order to obtain effective heat transfer with low pressure loss. Treuren et al [17], Rhee et al [18], Kanokjaruvijit and Martinez-botas [19] and Huang and his colleagues [20,21] investigated detailed heat transfer distributions under arrays of jet impinging on a target plate with dimpled or film hole surfaces. However, their studies only focused on the heat transfer under in-line arrays of jet impinging on a surface.…”
Section: Introductionmentioning
confidence: 99%